Gis-Based Non Point Source Pollution Modelling Of Sg. Selangor Basin - Ong, You Shu (2002)
Non Point Source (NPS) pollution is a diffuse pollution and regarded as one of the major pollution affecting the quality of water. It is yet to be taken into consideration in managing the water quality of river basin in Malaysia. Geographic Information System (GIS) is used to study the pollution since the sources and the spread involved spatial characteristic. Sg. Selangor basin has been chosen as the study area. Assessment of NPS pollution was conducted based on three parameters namely Biochemical Oxygen Demand (BOD), Total Nitrogen (TN) and Suspended Solids (SS). Runoff and land use are considered as the major factors contributing to the NPS pollution since NPS pollution travels through land area before reaching the stream network. The generated runoff was based on rainfall data and runoff coefficient. Stream network generation will be produced from digitized topographic maps where threshold values were tested. Expected Mean Concentration (EMC) values, associated with land use were extracted from literatures and research works and used to estimate the loading of pollutants in that area. Data from two sampling stations operated by the Department of Environment, i.e. 3517605 (upstream) and 3516604 (downstream) were to determine the level of NPS pollution. Annual accumulation of NPS pollutions were determined where the cumulative loadings of pollutants were compared with the computed observed values at the two sampling stations. Results for BOD showed that the differences of computed observed values exceeded generated values by 50.1 % at the upstream station and by 9.2% at the downstream station. For SS, there is a 38.9% difference at upstream and 38.6% differences at downstream. However, there was a wide variation in TN results with 67.2% differences in upstream and -39.1% in downstream. These variations are mainly due to limitations that are related to theoretical EMC values.